Paracellular Filtration Secretion Driven by Mechanical Force Contributes to Small Intestinal Fluid Dynamics - Randal K. Buddington; Thomas Wong; Scott C. Howard (Medical Sciences, 2021)
Studies of fluid secretion by the small intestine are dominated by the coupling with ATP-dependent generation of ion gradients, whereas the contribution of filtration secretion has been overlooked, possibly by the lack of a known mechanistic basis. We measured apical fluid flow and generation of hydrostatic pressure gradients by epithelia of cultured mouse enterocytes, Caco-2 and T-84 cells, and fibroblasts exposed to mechanical force provided by vigorous aeration and in response to ion gradients, inhibitors of ion channels and transporters and in vitro using intact mouse and rat small intestine. We describe herein a paracellular pathway for unidirectional filtration secretion that is driven by mechanical force, requires tight junctions, is independent of ionic and osmotic gradients, generates persistent hydrostatic pressure gradients, and would contribute to the fluid shifts that occur during digestion and diarrhea. Zinc inhibits the flow of fluid and the paracellular marker fluorescein isothyocyanate conjugated dextran (MW = 4 kD) across epithelia of cultured enterocytes (>95%; p < 0.001) and intact small intestine (>40%; p = 0.03). We propose that mechanical force drives fluid secretion through the tight junction complex via a “one-way check valve” that can be regulated. This pathway of filtration secretion complements chloride-coupled fluid secretion during high-volume fluid flow. The role of filtration secretion in the genesis of diarrhea in intact animals needs further study. Our findings may explain a potential linkage between intestinal motility and intestinal fluid dynamics.